Kepastian Hukum Dana Hibah Yayasan Yang Dialihfungsikan Oleh Pengurus Yayasan - Ramadhan, Muhammad Ilham; Hutomo, Putra; Marniati, Felicitas Sri (Postgraduate of Jayabaya University, 2023)
Grants to social organizations that are Indonesian legal entities as intended in Article 3 paragraph (1) letter d are given to social organizations or foundation that legitimately have legal entities or social organizations that are association legal entities that have received legal entity approval from science in the field of law and human rights following legislation. However, a phenomenon that occurs in society is that grants received by foundations are not used for activities or foundation interests, but are used by foundations for personal interests. What are the legal consequences of foundation grants being diverted by foundation administrators for personal interests? And what is the legal certainty about foundation grant funds being diverted by foundation administrators for personal interests? The theories used are Soeroso’s Law Consequences Theory and Jan Michiel Otto’s Legal Certainty.